Do home modifications reduce care home admissions for older people? A matched control evaluation of the Care & Repair Cymru service in Wales. (18th September 2020) - Hollinghurst, Joe; Fry, Richard; Akbari, Ashley; Watkins, Alan; Williams, Neil; Hillcoat-Nallétamby, Sarah; Lyons, Ronan A; Clegg, Andrew; Rodgers, Sarah E
Abstract: Background: home advice and modification interventions aim to promote independent living for those living in the community, but quantitative evidence of their effectiveness is limited. Aim: assess the risk of care home admissions for people with different frailty levels receiving home advice and modification interventions against a control group who do not. Study design and setting: matched control evaluation using linked longitudinal data from the Secure Anonymised Information Linkage (SAIL) Databank, comprising people aged 60–95, registered with a SAIL contributing general practice. The intervention group received the Care & Repair Cymru (C & RC) service, a home advice and modification service available to residents in Wales. Methods: frailty, age and gender were used in propensity score matching to assess the Hazard Ratio (HR) of care home admissions within a 1-, 3- and 5-year period for the intervention group ( N = 93, 863) compared to a matched control group ( N = 93, 863). Kaplan–Meier curves were used to investigate time to a care home admission. Results: the intervention group had an increased risk of a care home admission at 1-, 3- and 5-years [HR (95%CI)] for those classified as fit [1-year: 2.02 (1.73, 2.36), 3-years: 1.87 (1.72, 2.04), 5-years: 1.99 (1.86, 2.13)] and mildly frail [1-year: 1.25 (1.09, 1.42), 3-years: 1.25 (1.17, 1.34), 5-years: 1.30 (1.23, 1.38)], but a reduced risk of care home admission for moderately [1-year: 0.66 (0.58, 0.75), 3-years: 0.75 (0.70, 0.80), 5-years: 0.83 (0.78, 0.88)] and severely frail individuals [1-year: 0.44 (0.37, 0.54), 3-years: 0.54 (0.49, 0.60), 5-years: 0.60(0.55, 0.66)]. Conclusions: HRs indicated that the C & RC service helped to prevent care home admissions for moderately and severely frail individuals. The HRs generally increased with follow-up duration.